The AALAM/UWMCED Index of African American Well-Being in the Nation’s Largest Metropolitan Areas - (:unkn) unknown (My University, 2020)
This report, prepared for the African American Leadership Alliance MKE (AALAM), presents an index of African American community well-being in Milwaukee and the nation’s 50 largest metropolitan areas. The index is based on Black community status for each metro area on 30 indicators of community well-being, in areas such as employment; income, poverty, and social conditions; community health; and conditions for youth and children. Ranks on all of the component indicators were then synthesized into a composite index, ranking each of the nation’s largest metropolitan areas on the wellbeing of their respective African American communities. This study finds, on almost all indicators examined, that Black Milwaukee consistently ranks at or near the bottom compared to African American communities in large metropolitan areas across the country. On the composite index of African American well-being, Milwaukee ranks worst, by a fairly wide margin. The AALAM aims “to redefine Milwaukee as a top-ranking city for African Americans by 2025.” This study reveals the magnitude of that challenge.